Description of Leishmania (Leishmania) forattinii sp. n., a new parasite infecting opossums and rodents in Brazil - Yoshida, Elizaide L. A. [UNESP]; Cuba, Cesar A Cuba; Pacheco, Raquel da Silva; Cupolillo, Elisa; Tavares, Celso Cruz; Machado, Gerzia M. C.; Momen, Hooman; Grimaldi Junior, Gabriel (Instituto Oswaldo Cruz, Ministério da Saúde, 1993)
A new parasite species of Leishmania is described, L. (Leishmania) forattinii sp. n., which was isolated from a pooled triturate of liver and spleen of a opossum (Didelphis marsupialis aurita) and from skin samples from a rodent (Proechmys iheringi denigratus), captured in primary forest on the Atlantic Cost of Brazil. Our results on the basis of biological and molecular criteria indicate that this taxonomically distinct parasite ias a new species of the L. mexicana complex, but closely related to L. (L.) aristidesi Laison & shaw, 1979, as revelated by phenetic and phylogenetic numerical analyses of the enzyme data. L. forattinii was clearly distinguishable from other Leishmania species of the genus usisng enzyme electrophoresis, monoclonal antibodies, molecular karyotypes, analysis of restriction enzyme digestion patterns of kinetoplast DNA (kDNA), as well as the use of kDNA hybridization procedures.
Keywords: Leishmania (L.) forattinii sp. n.; Protozoa; Kinetoplastida; Trypanosomatidae; mammalian resevoirs; molecular characterization; monoclonal antibodies; isoenzyme electrophoresis; kenetoplast DNA analysis; molecular karyotype analysis